Tagansky Complex of Monuments of the Golden Horde Period on the Bityug River - Tsybin Mikhail V. (Археология евразийских степей, 2022)
The paper presents the results of a study of the Tagansky complex of monuments of the Golden Horde period on the Bityug River in the Pavlovsky District of Voronezh Oblast. The complex includes a subsoil burial ground, a settlement associated with it, as well as a settlement near Antipovka village. The study was carried out in 1995, 1998–2002 by an expedition of Voronezh State University. The ceramic complex includes pottery manufactured in the Golden Horde centers and Russian ceramics. The economic activity of the population includes agriculture, cattle breeding and metallurgical production. The morphology of skulls from the Tagansky burial ground finds analogies among the substrate Europeoid populations of Eastern Europe.